2016
DOI: 10.1007/s10722-016-0421-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wild tomato accessions (Solanum spp.) for resistance to two-spotted spider mite (Tetranychus urticae Koch) based on trichome type and acylsugar content

Abstract: Tomato wild relatives are important sources of resistance to many pests of cultivated tomato [Solanum lycopersicum L. (syn. Lycopersicon esculentum Mill.)]. Eleven wild tomato accessions previously identified at AVRDC-The World Vegetable Center as resistant to Bemisia tabaci were evaluated for resistance to the two-spotted spider mite [Tetranychus urticae (Koch.)] based on egg numbers using the leaf disc and Tanglefoot no-choice bioassays, and damage scores in choice bioassays. Highest resistance based on choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 48 publications
4
52
0
3
Order By: Relevance
“…This indicates that, although the same QTL is found to affect adult survival of both whitefly species, there may be more experimental noise in the survival data of T. vaporariorum . A possible cause for this additional noise may be that T. vaporariorum is stronger than B. tabaci, making it occasionally possible for T. vaporariorum to escape from the leaf even though it was “glued” by the sticky content of the type IV trichomes (Rakha et al 2017a; Vosman et al 2018). Alternatively, some compounds related to the resistance may have a more detrimental effect on B. tabaci than on T. vaporariorum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that, although the same QTL is found to affect adult survival of both whitefly species, there may be more experimental noise in the survival data of T. vaporariorum . A possible cause for this additional noise may be that T. vaporariorum is stronger than B. tabaci, making it occasionally possible for T. vaporariorum to escape from the leaf even though it was “glued” by the sticky content of the type IV trichomes (Rakha et al 2017a; Vosman et al 2018). Alternatively, some compounds related to the resistance may have a more detrimental effect on B. tabaci than on T. vaporariorum .…”
Section: Discussionmentioning
confidence: 99%
“…Leaf trichomes were shown to play a critical role in the interaction with pests. Several lines of evidence show that the glandular trichome type IV is particularly important in resistance against insects (Firdaus et al 2012; Muigai et al 2003; Rakha et al 2017a, c; Simmons et al 2005). Trichome type IV occurs on some accessions of tomato wild relatives, including S. pennellii , S. habrochaites , S. galapagense and S. pimpinellifolium.…”
Section: Introductionmentioning
confidence: 99%
“…Solanum galapagense also was resistant to whitefly and spider mite (Rakha et al., , ), and tomato fruitworm ( Helicoverpa armigera Hübner) tested in Taiwan at WorldVeg headquarters (Asif et al. unpublished data), indicating that resistance in this accession extends to multiple insects—a valuable finding.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the insect was first reported in sub-Saharan Africa and subsequently spread into Tanzania, Uganda and Kenya, where it has become a serious pest of field and greenhouse tomato production (Tonnang et al, 2015). Previous WorldVeg studies found glandular trichome-based resistance to whitefly and spider mite in certain accessions of S. cheesmaniae, S. galapagense and S. pimpinellifolium (Rakha et al, 2017a(Rakha et al, , 2017b, and the present study aimed to evaluate these seven accessions for resistance to T. absoluta in choice and no-choice feeding bioassays.…”
Section: Worldveg Trialsmentioning
confidence: 99%
See 1 more Smart Citation